Suppression of T-cell functions by human granulocyte arginase - Munder, Markus; Rudolph, Henriette; Luckner-Minden, Claudia; Giese, Thomas; Langhans, Claus-Dieter; Fuentes, Jose M.; Kropf, Pascale; Mueller, Ingrid; Kolb, Armin; Modolell, Manuel; Ho, Anthony Dick (Blood, 2006)
Chronic inflammation is accompanied by impaired T-cell immunity. In the mouse, myeloid cell-associated arginase accounts for the suppression of immune reactivity in various models of tumor growth and chronic infections. Here we show that arginase I is liberated from human granulocytes, and very high activities accumulate extracellularly during purulent inflammatory reactions. Human granulocyte arginase induces a profound suppression of T-cell proliferation and cytokine synthesis. This T-cell phenotype is due to arginase-mediated depletion of arginine in the T-cell environment, which leads to CD3ζ chain down-regulation but does not alter T-cell viability. Our study therefore demonstrates that human granulocytes possess a previously unanticipated immunosuppressive effector function. Human granulocyte arginase is a promising pharmacologic target to reverse unwanted immunosuppression.